Elevated corrosion in strain hardened AlMg alloy. (November 2018) - Neetu,; Singh, Subhash; Rao, P. Nageshwar; Jayaganathan, R.; Midathada, A.; Verma, Kartikey; Ravella, Uday K.
Abstract: Al-4.17 Mg (Al 5080) alloy was processed by multi axial forging (MAF) at room temperature up to cumulative strain of 4.2 in the present work. Mechanical properties of the alloy were investigated through Vickers hardness test and tensile test. Corrosion studies were carried on standard, forged and forged & annealed samples using 3.5% NaCl solution employing both Potentiodynamic polarization and immersion method. Microstructural evolution was studied on all the three samples using characterization techniques such as optical microscopy, electron backscattered diffraction, scanning electron microscopy and transmission electron microscopy. On a sample subjected to MAF, improvement in the strength and hardness was observed along with the significant drop in the corrosion resistance. However, when the same sample was further annealed, corrosion resistance was not only retained, but improved drastically. This odd behavior of this alloy was never reported earlier. The improved corrosion resistance of this alloy was discussed in light of surface profile along with the microstructural features. Highlights: Al-4.17 Mg (Al 5080) alloy was processed by multi axial forging (MAF). TEM micrograph shows average grain size of 320 nm. Potentiodynamic test shows that corrosion rate increased. Immersion test result shows the pit formation on the surface of the forged alloy.